Paleoenvironmental changes during the Late Pleistocene in Buenos Aires province (Argentina), using foraminifera fauna as proxy data - Petriella, Julieta (2023)
This paper describes the lithological and micropaleontological characteristics of a new record corresponding to the last interglacial for Buenos Aires province. Foraminifera were analyzed from an artificial outcrop 4 m thick (36◦34′0.97″ S and 57◦22′54.43″ W), from the quarry situated in the town of General Conesa, Buenos Aires province at an approximate elevation of 4 m a.s.l. Benthic foraminifera fauna was constituted by a predominance of calcareous forms represented mostly by the species Buccella peruviana and Ammonia parkinsoniana. The micropaleontological and lithological characteristics of all the sedimentary units involved in this locality suggest deposits associated with a transition from a low-energy shallow intertidal or subtidal zone to a higher-energy beach or supratidal environment. Although, the topographic height does not enable conclusive assignment of the age of this coastal deposit (>79.500 kyr), the environmental conditions could be correlated with the penultimate transgressive event that occurred at the beginning of the Late Pleistocene (MIS 5), which would have occurred in a shallow environment with changes in the marine influence. These findings provide new information that contributes to better understanding of the paleoenvironmental evolution of this region where two marine transgressions and two wind deposits have been recognized.